Fucoxanthin and Phenolic Contents of Six Dictyotales From the Tunisian Coasts With an Emphasis for a Green Extraction Using a Supercritical CO2 Method - Ktari, Leila; Mdallel, Cheima; Aoun, Brahim; Chebil Ajjabi, Leila; Sadok, Saloua (Frontiers in Marine Science, 2021)
Dictyotales, a common taxonomic group of brown seaweeds found in warm and temperate waters, are known for their richness in bioactive metabolites. In this study, six species of Dictyotales (Dictyopteris polypodioides, Dictyota dichotoma, Dictyota fasciola, Dictyota spiralis, Padina pavonica, and Taonia atomaria) collected from the Tunisian coasts were investigated for their antioxidant potentials, based on their contents of high added-value bioactive metabolites such as fucoxanthin and polyphenols. Fuxoxanthin and polyphenols were analysed quantitatively by HPLC and UV-spectrophotometer respectively. Antioxidant property of extracts was also determined based on their ability to scavenge DPPH’s free radical. Thus the highest concentrations of fucoxanthin, were obtained from Taonia atomaria and Dictyopteris polypodioides (5.53 ± 1.2 and 3.43 ± 1.3 mg.g-1 dry weight respectively), while the lowest amount from Dictyota spiralis (0.23 ± 0.1 m mg.g-1 dry weight). Dictyota dichotoma and Taonia atomaria gave the highest total phenol content (19.3 ± 0.4 and 15.2 ± 1.1 mg GAE.g-1 dry weight respectively). In a second step, Supercritical Carbon Dioxide (ScCO2) was used as a green and environmentally safe technique for the extraction of fucoxanthin from the most abundant species Dictyopteris polypodiodes. The extraction of fucoxanthin by ScCO2 allowed an extraction yield ranging from 0.50 ± 0.04 to 1.32 ± 0.02 % with 60°C temperature and 50 MPa pressure as the best extraction conditions. The maximum fucoxanthin and polyphenols recovery in the extract attained 15% and 64% respectively. The results strengthen the possible use of Dictyotales from Mediterranean Sea as a promising source of natural ingredients of health and economic interests contributing to Blue Growth in the region.